Spatial distribution and abundance of the giant tiger prawn, Penaeus monodon (Fabricius, 1798), in the Gulf of Urabá (Caribbean), Colombia, South America (2014)
ABSTRACT: The spatial distribution and abundance of the non-native giant tiger prawn Penaeus monodon (Fabricius, 1798) in the Gulf of Urabá, Colombian Caribbean, was examined using catch records made by trained fishermen. From 1 April to 30 November 2011, 397 individuals were recorded in 20 fishing localities in the Gulf. Individual weights ranged between 50 and 500 g (average 232 g). According to local fishermen, however, the giant tiger prawn has been present in the Gulf since 2007, possibly earlier. This non-native species was commonly captured along with the native white shrimp Litopenaeus schmitti (Burkenroad, 1936) in river mouths and mangrove habitat. The highest catches were from two sites near the Atrato river mouth (Boca del Roto, Boca del Leoncito) and one other site near the Turbo river mouth (Punta Yarumal). The effects of the giant tiger prawn, if it has become established, on the environment and the economy of the region areas is as yet unknown.